2006
DOI: 10.1534/genetics.105.051474
|View full text |Cite
|
Sign up to set email alerts
|

Segregating Variation in the Transcriptome:CisRegulation and Additivity of Effects

Abstract: Properties of genes underlying variation in complex traits are largely unknown, especially for variation that segregates within populations. Here, we evaluate allelic effects, cis and trans regulation, and dominance patterns of transcripts that are genetically variable in a natural population of Drosophila melanogaster. Our results indicate that genetic variation due to the third chromosome causes mainly additive and nearly additive effects on gene expression, that cis and trans effects on gene expression are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
68
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 40 publications
14
68
0
Order By: Relevance
“…Our observation that cis-and trans-eQTL are associated with different distributions of R 2 (Figure 2) was also found in Drosophila (Meiklejohn et al 2003;Wayne et al 2004;Hughes et al 2006). A potential explanation for this observation is that the transcript abundance of most genes is regulated by multiple signal transduction networks at multiple levels (e.g., transcription and transcript stability); thus a polymorphism in any one of these regulatory levels may be functionally limited to only a small change in transcript accumulation for those genes controlled in trans by that polymorphism.…”
Section: à14supporting
confidence: 74%
“…Our observation that cis-and trans-eQTL are associated with different distributions of R 2 (Figure 2) was also found in Drosophila (Meiklejohn et al 2003;Wayne et al 2004;Hughes et al 2006). A potential explanation for this observation is that the transcript abundance of most genes is regulated by multiple signal transduction networks at multiple levels (e.g., transcription and transcript stability); thus a polymorphism in any one of these regulatory levels may be functionally limited to only a small change in transcript accumulation for those genes controlled in trans by that polymorphism.…”
Section: à14supporting
confidence: 74%
“…Also, variation among the RILs reflects only the homozygous effects of alleles. Neither homozygous effects nor variation in the two parental lines is necessarily representative of variation segregating within randomly mating populations (Mackay 2001, Hughes et al 2006. If variation in sperm competition is maintained by strong balancing selection on a few loci, RILs generated from two inbred lines could fail to reflect variation that persists within randomly mating populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on regulatory elements have reported contrasting results regarding the overall proportions of cis vs trans effects, depending on the distance of the parental groups used to generate the crosses studied (interspecies or intraspecies) (Wayne et al, 2004;Wittkopp et al, 2004;Hughes et al, 2006;Lemos et al, 2008;Wittkopp et al, 2008b;Graze et al, 2009). However, most of these studies globally agree that cis regulation contributes more to gene expression variation than trans effects, especially in comparisons among populations relative to comparisons within populations.…”
Section: Cis-acting Regulatory Effectsmentioning
confidence: 99%